Pinus halepensis, Pinus pinaster, Pinus pinea and Pinus sylvestris Essential Oils Chemotypes and Monoterpene Hydrocarbon Enantiomers, before and after Inoculation with the Pinewood Nematode Bursaphelenchus xylophilus. Issue 1 (16th December 2016) - Rodrigues, Ana M.; Mendes, Marta D.; Lima, Ana S.; Barbosa, Pedro M.; Ascensão, Lia; Barroso, José G.; Pedro, Luis G.; Mota, Manuel M.; Figueiredo, A. Cristina
Abstract : Pinewood nematode (PWN), Bursaphelenchus xylophilus, is the causal agent of pine wilt disease, a serious threat to global forest populations of conifers, especially Pinus spp. A time‐course study of the essential oils (EOs) of 2‐year‐old Pinus halepensis, Pinus pinaster, Pinus pinea and Pinus sylvestris following inoculation with the PWN was performed. The constitutive and nematode inoculation induced EOs components were analyzed at both the wounding or inoculation areas and at the whole plant level. The enantiomeric ratio of optically active main EOs components was also evaluated. External symptoms of infection were observed only in P .  pinaster and P .  sylvestris 21 and 15 days after inoculation, respectively. The EO composition analysis of uninoculated and unwounded plants revealed the occurrence of chemotypes for P .  pinaster, P .  halepensis and P .  sylvestris, whereas P .  pinea showed a homogenous EO composition. When whole plants were evaluated for EO and monoterpene hydrocarbon enantiomeric chemical composition, no relevant qualitative and quantitative differences were found. Instead, EO analysis of inoculated and uninoculated wounded areas revealed an increase of sesquiterpenes and diterpenic compounds, especially in P .  pinea and P .  halepensis, comparatively to healthy whole plants EOs. Abstract :